2016
DOI: 10.1007/s00018-016-2312-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetically modified laboratory mice with sebaceous glands abnormalities

Abstract: Sebaceous glands (SG) are exocrine glands that release their product by holocrine secretion, meaning that the whole cell becomes a secretion following disruption of the membrane. SG may be found in association with a hair follicle, forming the pilosebaceous unit, or as modified SG at different body sites such as the eyelids (Meibomian glands) or the preputial glands. Depending on their location, SG fulfill a number of functions, including protection of the skin and fur, thermoregulation, formation of the tear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 251 publications
0
30
0
Order By: Relevance
“…Site‐specific differences in the morphology of SG and hair size and form as well as epidermal thickness are well established. To ascertain whether such site‐specific effects had been described in other reports, we searched for studies of mouse mutations which have affected SG size . This revealed that most laboratories restrict their observations to either tail or back skin.…”
Section: Discussionmentioning
confidence: 99%
“…Site‐specific differences in the morphology of SG and hair size and form as well as epidermal thickness are well established. To ascertain whether such site‐specific effects had been described in other reports, we searched for studies of mouse mutations which have affected SG size . This revealed that most laboratories restrict their observations to either tail or back skin.…”
Section: Discussionmentioning
confidence: 99%
“…There is also now evidence indicating that the SG serves important physiological roles, indicated by mouse models that lack SGs and sebaceous lipids . For example, mice that are genetically deficient for differentiated sebocytes exhibit impaired waterproofing of fur, are unable to regulate body temperature properly, and are more susceptible to ultraviolet radiation‐induced apoptosis in the epidermis and HFs .…”
mentioning
confidence: 99%
“…There is also now evidence indicating that the SG serves important physiological roles, indicated by mouse models that lack SGs and sebaceous lipids. 22 For example, mice that are genetically deficient for differentiated sebocytes exhibit impaired waterproofing of fur, are unable to regulate body temperature properly, and are more susceptible to ultraviolet radiation-induced apoptosis in the epidermis and HFs. 23 Sebum may also be required for maintaining skin barrier function, and loss of SGs is frequently associated with scarring alopecia in mice, [24][25][26] suggesting a role of SGs in HF maintenance.…”
mentioning
confidence: 99%
“…A number of additional mouse models have been identified naturally or created by genetic engineering with similar sequelae (Table ). However, not all mutated genes that are normally expressed in the sebaceous gland cause these diseases . For example, mice with mutations in Soat1, melanocortin 5 receptor ( Mc5r e ) and stearoyl‐coenzyme A desaturase 3 ( Scd3 ) do not exhibit follicular scarring, yet all these genes are expressed in the sebaceous gland.…”
Section: Animal Models For Primary Cicatricial Alopeciasmentioning
confidence: 99%